Responses of urine and blood biochemical markers to exercise-induced body fluid losses in elite Chinese road cyclists - Han, Q.; Fu, J.; Shao, J.; Wang, Q.; Fang, Z.; Gao, H.; Zhou, L.; Yi, M. (Exercise Biochemistry Review, 2018)
Objective To examine biochemistry parameters regarding exercise induced fatigue, e.g. Sweat Loss (SL), Creatine Kinase (CK), Lactate Dehydrogenase (LDH), Blood Urinary Nitrogen (BUN), etc.